Sensitivity Analysis for Deep Learning Data Sets Considering the Human Immune System - Takeda, Haruki; Miyamoto, Shoichiro; Zhou, Lei; Tamura, Yoshinobu; Yamada, Shigeru (Journal of Graphic Era University, 2024)
Recently, open source software (OSS) has been widely used in many fields due to the spread and development facilitated by networks. The characteristics of OSS include no cost and high performance, which make it a significant component of modern society. However, the number of reported faults is increasing due to its vulnerabilities. Detecting these faults requires substantial costs, and correcting the growing number of faults necessitates a large workforce. In this paper, we propose a method for Reliability Assessment of OSS using deep learning based on the human immune system. Additionally, we present several numerical examples based on the proposed method.